H.O. Penn : 'managing by values' brought the company back, but now will it guide its growth? - Barton-Sweeney, Alexandra, (SAGE knowledge. Cases., 2016)
In 1991, Tom Cleveland, CEO and owner of the Caterpillar dealership, H.O. Penn Machinery Company, found himself contemplating the sale of his poorly performing business, which had been in his family for nearly three decades. After he was unable to reach an agreement with a particular buyer, however, Cleveland re-committed himself to H.O. Penn, determined to turn around its fortunes. This study explains how Cleveland set about introducing a management system called 'Managing by Values', which would ultimately infuse explicitly stated values and goals into every facet of the company's operations.